Microhardness of Calcium-enriched Mixture Cement and Covering Glass Ionomers after Different Time Periods of Application - Jaber Ansari , Zahra; Ghasemi , Amir; Norozi , Hanieh; Akbarzade Baghban , Alireza; Samiei, Mohammad (Iranian Endodontic Journal, 2022)
Introduction: Various studies have recommended using calcium-enriched mixture (CEM) cement in different endodontic treatments, including vital pulp therapy. However, possible reciprocal effects of the covering glass ionomer cement (GIC) on their mechanical properties have not been yet investigated in detail. The current research aimed to experimentally evaluate the surface microhardness of CEM cement and the covering GICs after different application/testing times. Materials and Methods: Using stainless steel moulds (8×4×4 mm), CEM cement samples were prepared (n=120) and randomly divided into 12 experimental groups (n=10). CEM cement with thickness of 4 mm was inserted into the moulds, and the remaining spaces were filled with self-cured or light-cured resin-modified GICs at three-time intervals; immediate, in 15 min and after 24 h. Then, the samples were incubated for one and seven days. Using a Vickers microhardness tester, the microhardness of CEM and GICs was measured. The data were analyzed using two-way ANOVA and Tukey’s test, and the significance level was set at 5% (P<0.05). Results: The reciprocal effects of the type/time of application of GICs on the surface microhardness of CEM cement or GICs were statistically significant (P<0.001). The surface microhardness of CEM cement and both covering GICs significantly increased over time and in seven-day samples was significantly higher than in one-day samples (P<0.05). Conclusions: Low surface microhardness of CEM/GICs in short-term (24 h) seems transient; and appears to be compensated over a longer period (i.e. 7-day). Therefore, using GICs adjacent to CEM cement in single-visit restorative treatments may be advocated